ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI PADA PERUSAHAAN SEKTOR NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 - 2020 - Dhea Aulia Fitri, (2022)
This study aims to find out the differences in financial performance before and after mergers and acquisitions. The financial performance ratios measured in this study are the ratios of liquidity, solvency and profitability with an observation period of 1 year before and 1 year after mergers and acquisitions. The sample in this study is non-financial sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period and a total of 36 companies. This sampling technique uses a purposive sampling technique. The analysis technique of this study used the Friedman test. The results of this study indicate that there are no significant differences in the ratios of liquidity, solvency and profitability before and after mergers and acquisitions.